Exceptionalism - Jensen, Lars, author.
1 online resource
Keywords: "This book offers a concise mapping of the concept exceptionalism, interconnecting uses of exceptionalism typically studied in isolation from each other. Associated with narratives of nationhood that understand the country in terms of uniqueness, it is a term that has been utilised by leaders and pundits eager to confirm the preparedness of the nation to face challenges. This volume crucially provides an analytical and comparative approach, investigating the meaning and uses of the concept of exceptionalism, while demonstrating the ways in which it manifests itself in different historical and geographical settings. Exceptionalism offers comparative case studies from different parts of the world, showcasing the way in which exceptionalism has come to occupy an important narrative position in relation to different nation states, including the US, the UK, the Nordic countries, various European nations and countries in Latin America, Africa and Asia. An introduction to and overview of a term that has come to define the past and present identity of many nations, this book will appeal to scholars of sociology, anthropology, geography, cultural studies and politics"--